Construct Validity and Clinical Utility of World Health Organization Disability Assessment Schedule 2.0 in Older Patients Discharged From Emergency Departments - Nielsen, Louise Moeldrup; Oestergaard, Lisa Gregersen; Kirkegaard, Hans; Maribo, Thomas (Frontiers in Rehabilitation Sciences, 2021)
Abstract Introduction: The World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) is designed to measure functioning and disability in six domains. It is included in the International Classification of Diseases 11th revision (ICD-11). The objective of the study was to examine the construct validity of WHODAS 2.0 and describe its clinical utility for the assessment of functioning and disability among older patients discharged from emergency departments (EDs). Material and methods: This cross-sectional study is based on data from 129 older patients. Patients completed the 36-item version of WHODAS 2.0 together with the Barthel-20, the Assessment of Motor and Process Skills (AMPS), Timed Up and Go (TUG), and the 30-Second Chair Stand Test (30s-CST). Construct validity was examined through hypothesis testing by correlating the WHODAS 2.0 with the other instruments and specifically the mobility domain in WHODAS 2.0 with the TUG and 30s-CST tests. The clinical utility of WHODAS was explored through floor/ceiling effect and missing item responses. Results: WHODAS 2.0 correlated fair with Barthel-20 (r=-0.49), AMPS process skills (r=-0.26) and TUG (r=0.30) and correlated moderate with AMPS motor skills (r=-0.58) and 30s-CST (r=-0.52). The WHODAS 2.0 mobility domain correlated fair with TUG (r=0.33) and moderate with 30s-CST (r=-0.60). Four domains demonstrated floor effect: D1 ‘Cognition’, D3 ‘Self-care’, D4 ‘Getting along’ and D5 ‘Household’. Ceiling effect was not identified. The highest proportion of missing item responses were present for Item 3.4 (Staying by yourself for a few days), Item 4.4 (Making new friends), and Item 4.5 (Sexual activities). Conclusion: WHODAS 2.0 had fair-to-moderate correlations with Barthel-20, AMPS, TUG, and 30s-CST and provides additional aspects of disability compared with commonly used instruments. However, the clinical utility of WHODAS 2.0 applied to older patients discharged from EDs poses some challenges due to floor effect and missing item responses. Accordingly, patient and health professional perspectives need further investigation.